Rossijskij proletariat Oblik, bor'ba, gegemonija. [Sbornik statej. Avt.: M.S. Volin, P.V. Volobuev, P.I. Vorobej i dr. Otv. red.: L.M. Ivanov] ("Nauka", 1970)
Akademija nauk SSSR. Institut istorii SSSR.